The creation of Islamic trust under the civil requirements in Malaysia - Mohd Yusof, Yusnita (Usuli Faqih Research Centre PLT, 2024)
Trust is an exclusive creation. It covers both legal and equitable rights in a concept created by English jurists which is based on Common Law principles. The trust as applicable in Malaysia is for both non-Muslims and Muslims, without any exceptions. In Islam, trust is justified as a method of transferring the ownership of property from the owner to the beneficiaries. While the main reason for creating such a trust is to secure the rights of a beneficiary who has an issue with legal capacity, such as minor and lunatic, the instrument of trust has been used by the Muslims to augment the share that should be received by the beneficiaries after the death of the settlor, which has already been fixed by Islamic law. Hence, this article seeks to determine and compare the creation of civil and Islamic trust in Malaysia, including the jurisdiction of the court in this matter, if challenged. This article adopts a content analysis by examining the existing primary and secondary materials, including the statutory provisions and case law. It is observed that the jurisdiction of the civil court in matters relating to the Islamic trust should be reformed. In addition, codified guidelines on the creation of trust by Muslims through civil trust requirements are highly necessary in order to ensure that the trust does not violate Islamic principles.